2020
DOI: 10.3390/d12100377
|View full text |Cite
|
Sign up to set email alerts
|

Range-Wide Population Assessment of the Endangered Yellow-Naped Amazon (Amazona auropalliata)

Abstract: Yellow-naped amazons, Amazona auropalliata, have experienced a dramatic population decline due to persistent habitat loss and poaching. In 2017, BirdLife International changed the species’ status from threatened to endangered and estimated that between 10,000 and 50,000 individuals remained in the wild. An accurate estimate of the number of remaining wild individuals is critical to implementing effective conservation plans. Wright et al. conducted roost count surveys in Costa Rica and Nicaragua during 2016 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Our interviews revealed that Lilacine Amazons were trapped both in mangroves, where they roost, and dry forests, where they feed and nest [38,39], suggesting that both adults and chicks are being taken from the wild. Anecdotal reports from communities suggest past events of outsiders casting nets over mangrove islands to remove an entire roost of Lilacines at a time.…”
Section: Discussionmentioning
confidence: 93%
“…Our interviews revealed that Lilacine Amazons were trapped both in mangroves, where they roost, and dry forests, where they feed and nest [38,39], suggesting that both adults and chicks are being taken from the wild. Anecdotal reports from communities suggest past events of outsiders casting nets over mangrove islands to remove an entire roost of Lilacines at a time.…”
Section: Discussionmentioning
confidence: 93%
“…However, single counts at communal roosts, such as those performed here, do not allow for the identification of uncertainty in population size estimates related to detection errors, which may lead to the underestimation of real population numbers [67,68]. Despite these limitations, roost counts allow a reasonable lower bound for estimating the total population size (e.g., [66]) and its temporal changes (e.g., [68]) when individuals concentrate in well-known localities, thus reducing the probability of overlooking large flocks during census [68]. In the case of rose-ringed parakeets in Seville, we cannot discard small counting errors that may slightly affect annual population sizes, but they are overweighed by the easy locating of the largest roosts [47].…”
Section: Discussionmentioning
confidence: 86%
“…Monk parakeets, on the other hand, have grown exponentially but seem to have reached a stability of about 1500 individuals, distributed in several breeding nuclei scattered throughout the study area. Population censuses, through counts of individuals at roosts, are suitable for communal roosting species, such as some parrot species [44,[65][66][67][68]. However, single counts at communal roosts, such as those performed here, do not allow for the identification of uncertainty in population size estimates related to detection errors, which may lead to the underestimation of real population numbers [67,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While roost counts may allow estimating regional and even global populations sizes of some parrot species [11,60,62,63], they are not affordable for most parrot populations and species and thus estimates of densities are often obtained using point counts or walk line transects [10]. However, these methodologies may fail to record rare and patchily distributed species, a problem that could be solved using large-scale roadside car surveys [10].…”
Section: Discussionmentioning
confidence: 99%